Impact of social media disinformation explored in 'The Social Dilemma' - Rizky Aditya Husandani; Prahastiwi Utari; Andre Noevi Rahmanto (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2024)
This study explored the significant impact of disinformation spread through social media, focusing on the documentary "The Social Dilemma" by Jeff Orlowski. The film provided a critical lens to examine how social media algorithms amplified false narratives. Using a qualitative content analysis approach, the research highlighted key themes related to disinformation, such as political polarization in the U.S., the flat earth theory, the #Pizzagate conspiracy, Covid-19 misinformation, and the incitement of hate speech in Myanmar. The findings revealed that algorithms designed to maximize user engagement often prioritized sensational and misleading content, exacerbating the spread of false information. This fueled social tensions and undermined public health and democratic processes. The study emphasized the urgent need for increased public awareness of disinformation's effects and called on social media platforms to take responsibility for reducing its spread.